Computational study of the effect of fuel element geometry on pellets’ maximum temperature; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Vorobiev A. V. Aleksandr Vladimirovich (2017, 2017)
Title screen